The Estate of Stefan Koryciński, Grand Chancellor of the Crown (1653–1658) - Pielas, Jacek (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
The article presents the history of the estate of Stefan Koryciński, Crown Chancellor (1653–1658). It was established that after the division of the estate of his father. Koryciński inherited seven villages, then he increased the land, mainly after taking over the estate from his brother Mikołaj Ferdinand (1651). At the end of his life, his private property consisted of fourteen villages located in four provinces and two tenement houses in Krakow. It was emphasized that comparing to other figures of the 17th century political elite, it was a modest fortune, and the chancellor obtained the main part of his income from royal estates. After the chancellor’s death, his property was inherited by two sons: Piotr Mikołaj and Mikołaj Andrzej.